Aspergillus fumigatus NITDGPKA3 Provides for Increased Cellulase Production - Nibedita Sarkar; Kaustav Aikat (International Journal of Chemical Engineering)
A cellulolytic fungal strain, Aspergillus fumigatus NITDGPKA3, was isolated from straw retting ground. Cellulase and xylanase production by A. fumigatus NITDGPKA3 in submerged fermentation of rice straw was studied. The culture conditions for maximum enzyme production were found to be initial pH 4, 1% substrate concentration, temperature 30°C, incubation time 5 days, 0.2% tryptone as nitrogen source, and inoculum volumes 7% v/v (for cellulase) and 5% v/v (for xylanase). Addition of Tween 80 in fermentation broth improved xylanase production (193.58 IU/ml) much more compared to cellulase production (6.53 IU/ml). Xylanase activity found in the culture broth was approximately 50% higher compared to most of the reported data. The crude enzyme was further applied for reducing sugar production from alkali pretreated rice straw, where a dosage of 40 IU/g CMCase produced 0.522 g reducing sugar/g dry substrate after 36 hours which was higher than that in the reported literature. The high concentration of reducing sugar yield was most probably due to the extraordinarily high titer of β-glucosidase (80.1 IU/ml) found in the crude enzyme. The crude enzymes secreted by Aspergillus fumigatus NITDGPKA3 efficiently hydrolyzed alkali pretreated rice straw suggesting that Aspergillus fumigatus NITDGPKA3 is a robust microorganism.